EKOLOGI PEMBELAJARAN BERBASIS ARTIFICIAL INTELLIGENCE: REKONSTRUKSI PARADIGMA PENDIDIKAN TINGGI DI ERA DIGITAL - Danny Yonathan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of Artificial Intelligence (AI), particularly Generative AI, has profoundly reshaped the landscape of higher education. This transformation extends beyond the digitalization of teaching and learning, influencing how knowledge is created, shared, and reconstructed within academic environments. Despite the growing body of research on AI in higher education, most studies continue to frame AI primarily as a pedagogical tool for improving learning effectiveness. Consequently, limited attention has been given to understanding how AI reconfigures the broader learning ecology by reshaping the relationships among human actors, technology, academic culture, and institutional governance. This study aims to reconstruct the paradigm of higher education through the perspective of AI-based learning ecology by proposing the AI Learning Ecology Framework as a conceptual model. Employing a qualitative approach with a library research method and an integrative literature review design, this study synthesizes evidence from internationally indexed journals, SINTA-accredited national journals, scholarly books, and official publications issued by UNESCO and the OECD. The collected literature was analyzed through thematic synthesis to identify recurring patterns, research gaps, and conceptual relationships. The findings indicate that the transformation of higher education should be understood as an ecological process shaped by the dynamic interaction of six interconnected components: human agency, intelligent technology, pedagogical design, academic culture, institutional governance, and ethical and humanistic values. Within this framework, AI is positioned as a cognitive partner that strengthens human capabilities rather than replacing the roles of educators and students. The study concludes that the successful integration of AI depends not merely on technological sophistication but on the ability of higher education institutions to cultivate an adaptive, collaborative, ethical, and human-centered learning ecology. The proposed AI Learning Ecology Framework offers a conceptual foundation for developing policies, curricula, and learning strategies that are responsive to the evolving demands of the digital era.